D-Dimer as a Prognostic Indicator in Critically Ill Patients Hospitalized With COVID-19 in Leishenshan Hospital, Wuhan, China - Li, Jinpeng; Liu, Zeming; Wu, Gaosong; Yi, Meilin; Chen, Yongfeng; Li, Kun; Xu, Xiaoming; Xiao, Linqi; Wu, Qian; Chen, Jincao; Wu, Xiaohui (Frontiers in Pharmacology, 2020)
Background: D-dimer is a small protein fragment and high levels of D-dimer have been associated with increased mortality in patients presenting to emergency departments with infection. Previous studies have reported increased levels of D-dimer in COVID-19; however, it is unclear whether an increased D-dimer level provides early warning of poor prognosis. Therefore, this study aimed to assess the usefulness of D-dimer as an early indicator of prognosis in patients with coronavirus disease (COVID-19). Methods: We conducted a retrospective study of patients with COVID-19 admitted to Leishenshan Hospital in Wuhan, China, from February 15 to March 30, 2020. The final date of follow-up was April 11, 2020. Results: Of the 1643 patients with COVID-19, 691 had elevated D-dimer levels. Their median age was 65 years. Of the patients with elevated D-dimer levels, 45% had comorbidities, with cardiovascular disease (205 [29.7%]) being the most common. Patients with elevated D-dimer were more likely to require treatment with high-flow oxygen, anticoagulation, antibiotics, and admission to the intensive care unit (ICU). They were also more likely to have increased interleukin-6, monocytes, and lymphocytes. Patients with elevated D-dimer levels had significantly higher mortality than those with normal or low D-dimer levels. Conclusions: In patients with COVID-19, elevated D-dimer was associated with abnormal immunity, underlying disease, increased disease severity, and increased mortality. Taken together, D-dimer may be a marker for the early warning of disease severity and increased risk of death. These findings provide insights into the potential risk of elevated D-dimer in patients with COVID-19.